Implementasi Pendekatan Saintifik dalam Pembelajaran Ilmu Pengetahuan Alam untuk Meningkatkan Hasil Belajar Siswa SD Negeri 15 Karya Sempurna - Ritonga , Nurliati; Baria , Hairul; Kaseh, Kaseh (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to analyze the implementation of the scientific approach in Natural Science (IPA) learning to improve students' learning outcomes at SD Negeri 15 Karya Sempurna. This research employs a Classroom Action Research (CAR) method conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 30 fifth-grade students. Data collection techniques included learning outcome tests, observations, and documentation. The results showed that the implementation of the scientific approach significantly improved students' learning outcomes. In the first cycle, the average student score was 70, while in the second cycle, it increased to 85. This improvement indicates that the scientific approach effectively helps students understand science concepts more deeply through the processes of observing, questioning, experimenting, reasoning, and communicating. Therefore, the scientific approach is recommended as an innovative learning strategy to enhance students' learning outcomes at the elementary school level.